The Relationship Between Psychosocial Factors and Response to Epidural Steroid Injection for Chronic Lumbosacral Radicular Pain: A Prospective Pilot Study - Stensland M; Sanford E; Houle TT; McGeary C; Cobos BA; Lugosi S; Lehman L; Nabity PS; Covell C; Fitzgerald E; Mojallal M; Reed DE; et al. (Journal of Pain Research)
Meredith Stensland,1,2 Elizabeth Sanford,1,2 Timothy T Houle,3 Cindy McGeary,1,2 Briana A Cobos,1 Selena Lugosi,4 Luke Lehman,5 Paul S Nabity,1,2 Caleigh Covell,1 Elizabeth Fitzgerald,1 Mahsa Mojallal,1 David E Reed,6,7 Sanjog Pangarkar,8,9 Blessen C Eapen,8,9 Udai Nanda,8,9 Zachary L McCormick,10 Donald McGeary1,2,11 1Department of Psychiatry and Behavioral Sciences, University of Texas Health Science Center at San Antonio, San Antonio, TX, USA; 2South Texas Veterans Health Care System, Department of Veterans Affairs, San Antonio, TX, USA; 3Department of Anesthesia, Massachusetts General Hospital, Boston, MA, USA; 4School of Medicine, University of Texas Health Science Center at San Antonio, San Antonio, TX, USA; 5Department of Rehabilitation Medicine, University of Texas Health Science Center at San Antonio, San Antonio, TX, USA; 6Department of Psychiatry and Behavioral Sciences, University of Washington, Seattle, WA, USA; 7Seattle-Denver Center of Innovation (COIN) for Veteran-Centered and Value-Driven Care, U.S. Department of Veterans Affairs, Seattle, WA, USA; 8Department of Physical Medicine & Rehabilitation, VA Greater Los Angeles Healthcare System, Los Angeles, CA, USA; 9Department of Medicine, UCLA, Los Angeles, CA, USA; 10Department of Physical Medicine and Rehabilitation, University of Utah School of Medicine, Salt Lake City, UT, USA; 11Department of Psychology, University of Texas at San Antonio, San Antonio, TX, USACorrespondence: Meredith Stensland, Department of Psychiatry and Behavioral Sciences, University of Texas Health Science Center at San Antonio, 5788 Eckhert Road, San Antonio, TX, 78240, USA, Tel +1-515-681-0459, Email stensland@uthscsa.eduPurpose: Chronic lumbosacral radicular pain is a disabling condition commonly treated with epidural steroid injections (ESIs). Extant research suggests that psychosocial factors impact clinical outcomes among patients with back pain. The purpose of this study is to examine the relationship between psychosocial variables and post-injection pain intensity.Setting: Interventional pain management clinic.Methods: A prospective longitudinal cohort study with repeated within-subject measures. Assessment timepoints included a pre-injection baseline, immediately post-injection, 6 weeks, and 12 weeks, and 6 months; patients completed a battery of self-report assessments at each point. The primary outcome was pain intensity (numeric rating scale 0– 10). Data were analyzed using principal component analysis and generalized linear mixed-effects modeling.Results: A total of 40 patients (age 52 ± 13.05) participated in this study. Higher pre-injection pain was predictive of higher post-injection pain at all time points (p< 0.001). Controlling for baseline pain and demographics, those with Negative Affect 1 standard deviation higher at baseline reported a 1.12-point mean higher pain rating at 12 weeks than those with lower Negative Affect (95% CI: 0.18– 2.07; p=0.020), while those with Cognitive Resilience 1 standard deviation higher at baseline had a 1.12-point mean lower pain rating at 6 months post-injection (95% CI: − 2.09 − 0.05, p=0.040).Conclusion: Patients with higher negative affect and lower cognitive resilience achieve less pain improvement after ESIs for low back pain. Future research with a larger sample should focus on deepening our understanding of the role of psychosocial functioning as a potential mechanism of treatment response in patients undergoing ESI procedures. Findings point to the importance of multidisciplinary chronic pain care.Keywords: epidural steroid injection, chronic low back pain, radiculopathy, psychosocial